2014
DOI: 10.1002/chem.201405770
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Pentasaccharide and Neoglycoconjugates Related to Fungal α‐(1→3)‐Glucan and Their Use in the Generation of Antibodies to Trace Aspergillus fumigatus Cell Wall

Abstract: Who designed the cover?The cover-page was conceptualized by Nikolay. Bohzena, Maria and Vishukumar contributed mainly to the design and production of the cover. Jean-Paul provided the beautiful microphotograph of A. fumigatus.What is the most significant result of this study?Development of an approach to the synthesis of long enough a-(1!3)-linked glucose oligomers. Despite the tremendous progress in glycosylation methodology during past decades, highly stereoselective preparation of a-glycosides is still a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies found that using biotinylated capsular polysaccharide of S. pneumoniae type IV (b-CPS4) noncovalently bound to Psp/Psa-SA was sufficient to produce a superior humoral and cellular immune response as compared to the protein antigen alone [ 146 , 147 ]. This strategy can be further extended to other antigenic carbohydrates, limited only by the availability or generation of biotinylated species [ 148 , 149 ] in the case of the biotin-SA system. This approach may be generally extendable to other carrier molecules and/or modular binding partners when suitable for development of a particular vaccine.…”
Section: Therapeutics That Are Enhanced By Protein Conjugationmentioning
confidence: 99%
“…Studies found that using biotinylated capsular polysaccharide of S. pneumoniae type IV (b-CPS4) noncovalently bound to Psp/Psa-SA was sufficient to produce a superior humoral and cellular immune response as compared to the protein antigen alone [ 146 , 147 ]. This strategy can be further extended to other antigenic carbohydrates, limited only by the availability or generation of biotinylated species [ 148 , 149 ] in the case of the biotin-SA system. This approach may be generally extendable to other carrier molecules and/or modular binding partners when suitable for development of a particular vaccine.…”
Section: Therapeutics That Are Enhanced By Protein Conjugationmentioning
confidence: 99%